Ecotoxicological insights: Utilizing bullfrogs (Lithobates catesbeianus) as experimental tools in the 21st century - Ferreira, Claudia Maris; Marcantônio, Adriana Sacioto; Viriato, Cristina [UNESP]; França, Fernanda Menezes; de Mello, Mikel Eduardo (My University, 2025)
Ecotoxicology is a science that studies the toxic effects of pollutants on ecosystems. Toxicology guidelines for the 21st century point to a trend toward less invasive practices and the incorporation of the principles of the 3 R's (Replacement, Reduction, and Refinement) for sentient animals. In this sense, amphibians are exceptional indicators of environmental change due to their high plasticity and adaptability, responding to the pressures of aquatic and terrestrial contaminants. Among them, the bullfrog (Lithobates catesbeianus) is an important bioindicator and an excellent experimental model, as it is distributed worldwide and resists the constraints of animal maintenance and experimentation. This species has been used in research by the ecotoxicology group of the Instituto de Pesca in Brazil since 1998. With this species, we use different biomarkers to monitor diseases and biological processes in anurans, assess the environmental health of ecosystems and, above all, evaluate the harmful effects of chemical substances. Over the years, we have started to use L. catesbeianus in less sentient phases, such as the embryonic stage, for ecotoxicology tests (FETAX test). We also conduct behavioral studies to investigate the responses to chemical interventions in the environment (avoidance test). In this chapter, we not only present a consolidation of our research results but also discuss the need for high-throughput testing strategies.
Keywords: Avoidance; Biomarker; Experimental model; FETAX; Model organism; Principle of the 3 R's